Evaluation of the environmental impact due to the raising of trout in the Aricota lagoon, Tacna - Castro Machaca, Yemile Rocio del Carmen (2022)
The investigation was carried out in the Aricota lagoon, located in the Tacna region. The environmental impact generated by the raising of trout fingerlings, which is carried out in an artisanal way in floating cages, was evaluated through the Rapid Impact Assessment Matrix methodology (RIAM). The physical, biological and socio-economic components that are affected were identified. The physical, chemical and microbiological parameters and metals were also determined by Inductively Coupled Plasma Mass Spectrometry in a certified laboratory. The results indicate that the negative environmental impacts are classified as moderate negative impact, as the water quality of the lagoon does not show signs of organic or biological contamination. However, when analyzing the total metals, high values of arsenic were found (0.672 ± 0. 0056 mg/L), and boron (8.78 ± 0.2687 mg/L) compared to those established by the Environmental Quality Standards (ECA) for this type of water bodies. Finally, according to the amount of phosphorus (0.08 ± 0.0141 mg/L) found, the lagoon is classified as eutrophic according to the Vollenweider classification.